Desenvolvimento de um modelo de simulação para identificação de gargalos na cadeia de suprimentos de uma empresa de mineração - Oliveira Júnior, Roberto (2011)
The objective of this work is to develop a methodology to identify bottlenecks in the supply chain of inputs for the mining industry, more specifically to the process of pelletizing or agglomeration of fine iron ore pellets. This methodology is based on computer modeling and simulation of supply chain and the definition of appropriate indicators to assess their logistics performance. A model of discrete event simulation was developed to represent the current configuration of the supply chain, focusing on highlighting the main processes that comprise it. Taking as a base, variations of the model were built in the form of experiments, to evaluate and verify the effectiveness of alternative configurations in different possible scenarios for the whole system. The importance of the proposed theme is the lack of academic research focusing on the Brazilian mining sector and, more specifically, the input supply chain of production processes involving suppliers and customer. The current academic collection is more focused on the process of distribution of finished products, involving producers, wholesalers, retailers and end customers. The results obtained in the experiments proved prescient when confronted with reality, the proposed methodology is developed and proved effective as a tool to support analysis and decision making in such studies.